PENGARUH INFLASI DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI KOTA PALANGKA RAYA - Erlina Lumbanraja; Nurafny Indrawati, Mahdalena, Thymothy Segah Alexander Rupock, Suherman Juhari (CV. Adiba Aisha Amira, 2024)
This study aims to see the effect of inflation, population on the growth of Palangka Raya city. The data used in this study were taken from 2018-2022 through annual data. The data model used in this study is secondary time series data obtained from the central statistics agency (BPS) Palangka raya. In this study, the formulation of associative problems with causal relationships of the causal introduction type is used in quantitative analysis because (X) and (Y) are independent and dependent variables that can influence and be influenced by each other. Multiple linear regression analysis and hypothesis testing with IBM SPSS statistics 25 analysis tools and the Ordinary Least Square (OLS) method are the data analysis models used in this study. This research will direct the extent to which the influence of inflation and population will affect the economic growth of Palangka Raya. If inflation is high and uncontrollable, or if the population increases but is not accompanied by adequate infrastructure development or employment, economic growth can be hampered. Conversely, if there are appropriate policies to control inflation and utilize population growth effectively, this can support better economic growth.